2015
DOI: 10.1038/srep12172
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the extinction of Ebola spreading in Liberia due to mitigation strategies

Abstract: The Ebola virus is spreading throughout West Africa and is causing thousands of deaths. In order to quantify the effectiveness of different strategies for controlling the spread, we develop a mathematical model in which the propagation of the Ebola virus through Liberia is caused by travel between counties. For the initial months in which the Ebola virus spreads, we find that the arrival times of the disease into the counties predicted by our model are compatible with World Health Organization data, but we als… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 27 publications
1
30
0
Order By: Relevance
“…Based on local information, a susceptible individual interrupts the contact with an infected individual with a certain probability and restores it after a fixed period of time. In a similar way [36], extended the model and was able to successfully predict the date of extinction of the Ebolaʼs outbreak in Liberia in 2014. Ebola outbreaks have been studied by the scientific community due to the high impact of this epidemic on certain regions of southwest Africa, mainly in Guinea, Sierra Leona and Liberia.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Based on local information, a susceptible individual interrupts the contact with an infected individual with a certain probability and restores it after a fixed period of time. In a similar way [36], extended the model and was able to successfully predict the date of extinction of the Ebolaʼs outbreak in Liberia in 2014. Ebola outbreaks have been studied by the scientific community due to the high impact of this epidemic on certain regions of southwest Africa, mainly in Guinea, Sierra Leona and Liberia.…”
Section: Introductionmentioning
confidence: 98%
“…Ebola outbreaks have been studied by the scientific community due to the high impact of this epidemic on certain regions of southwest Africa, mainly in Guinea, Sierra Leona and Liberia. Fortunately, there exists available data for the scientific community enabling to study more accurately the behavior and propagation of this disease [36,37].…”
Section: Introductionmentioning
confidence: 99%
“…However, recent results have shown that these estimates are much larger than the true extent of the disease outcome [24]. This overestimate of late dynamics when using early dynamics has been raised by many authors in general cases, as well as specifically for the Ebola virus [25,26]. We build upon these known observations to show that even in fully mixed models, * louzouy@math.biu.ac.il the early dynamics cannot be used to estimate the outcome of the late dynamics, and we propose an alternative approach.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to comparing the modeling results with those derived from the WHO criteria, we examined how influential relatively unknown parameters are to determining the week in which the end of an epidemic can be declared. While the relevance of sexual transmission to the overall transmission dynamics has been explored elsewhere ( Abbate et al, 2016;Vinson et al, 2016 ), as has the extinction time of Ebola using a mathematical model ( Abbate et al, 2016;Valdez et al, 2015 ), the present study is the first to model the end of Ebola, explicitly accounting for sexual transmission.…”
Section: Discussionmentioning
confidence: 99%